Pembelajaran berbasis Teknologi Melalui Game based Learning Platform Wordwall pada Anak Usia Dini - Syofiyanti, Dessy; Pipit Aprilia Susanti; Martiani; Yolla Franssisca; Dwi Budiarti; Rahma Dwi Marta; Serli Hasmita (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the effectiveness of technology-based learning through the Wordwall game-based learning platform in early childhood education using the Systematic Literature Review (SLR) method. The study systematically reviewed ten national and international journal articles published between 2019 and 2025 that examined the application of Wordwall in early childhood learning. The selection process involved inclusion and exclusion criteria to ensure the relevance and quality of the reviewed studies. The results indicate that Wordwall is highly effective in enhancing children’s cognitive, language, and learning motivation aspects. It promotes active engagement, improves vocabulary mastery, and fosters logical thinking through interactive game-based activities. Moreover, Wordwall encourages teachers to design creative and child-centered learning experiences aligned with 21st-century digital competencies. Despite its advantages, several challenges remain, including limited digital infrastructure and teachers’ technological readiness in certain schools. Overall, the findings demonstrate that Wordwall serves as an adaptive, effective, and enjoyable digital learning innovation that supports holistic child development in early childhood education settings.